PKM Pendampingan Penyusunan Standar Pelayanan Publik Pada Masa Pandemi COVID-19 DI Desa Candinegara Kecamatan Pekuncen Kabupaten Banyumas - Ariesta Amanda; Thahrina Azriah (Jurnal Pengabdian Masyarakat Dharma Andalas, 2022)
Special service standards for pandemic conditions must be made considering the importance of the safety of service providers and beneficiaries of public services. The legal basis for regulations related to the COVID-19 pandemic disaster and Ministry of Health regulations that require the implementation of the COVID-19 protocol. Security and safety guarantees can be applied very strictly to avoid transmission. The preparation of SOPs can serve as a guideline to anticipate various unexpected situations that will be faced by the company (service offices), as well as a reference for carrying out work. In addition, SOPs can also be used as a legal basis in the event of irregularities in the company/public service provider.This Community Partnership Program is implemented on the basis of the urgent needs of partners to be able to realize public services in accordance with government regulations. One of them is the availability of Standard Operating Procedures (SOP) during the Covid-19 Pandemic for public services at the Candinegara Village Village Office, Pekuncen District, Banyumas Regency. The stages of assistance carried out are First, socializing the importance of the availability of SOPs for public services during a pandemic. Partners are given material related to the importance of the availability of Public Service SOPs during a pandemic. Second, training and assistance in the preparation of public service SOPs during a pandemic. Partners are given material related to the steps and stages of preparing the SOP for Public Services during the pandemic. Third, training and mentoring on strategies for formulating SOPs for public services during a pandemic that is effective and efficient. Partners are given material related to the strategy for formulating an effective and efficient SOP for Public Services during a pandemic.The results obtained from this community partnership program activity are the availability of a Public Service Standard Guide during the Covid-19 Pandemic in the form of Standard Operating Procedures. The SOP will later be used in the implementation of public service activities at the Candinegara Village Village Office, Pekuncen District, Banyumas Regency.